Implementasi Preservasi dan Konservasi Naskah Kuno di Perpustakaan Nasional: Analisis Proses, Tantangan dan Implikasi Sosial Terhadap Pelestarian Warisan Budaya Indonesia - Wijayanti, Adinda; Wibowo, Brilliant Rozzaq; Priadi, Deri Rahmat; Putri, Faura Allysa; Fathamy, Fayyaz Ammar; Kautsari, Mutiara Audri; Yosnadi, Nadia Sahira; Khaleeda, Vitaya Nur (Brand Communication, 2025)
The preservation and conservation of ancient manuscripts is an important effort in safeguarding Indonesia's cultural heritage. The National Library of the Republic of Indonesia (Perpusnas RI) plays an important role in protecting these precious documents through physical restoration and digital conversion. This research aims to analyze the implementation process, identify key challenges, and explore the social implications of manuscript preservation and conservation at Perpusnas RI. Using a qualitative descriptive-analytical approach, data was collected through content analysis of official documentary videos and supported by relevant literature. The results show that the preservation process involves specialized techniques, facilities, and skilled personnel. However, several challenges remain, including limited human resources, the lack of regional conservation facilities, and low public awareness. Socially, the process contributes to raising collective awareness about the importance of historical memory. Digitization efforts further democratize knowledge by making ancient manuscripts accessible to a wider audience, especially the younger generation. This research emphasizes the need for inclusive and sustainable strategies in manuscript preservation, highlighting collaboration between institutions and communities.